2017
DOI: 10.1016/j.jana.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Study on Correlates of HIV-Related Stigma Among Gay and Bisexual Men in the Southern United States

Abstract: Societal prejudice against people living with HIV infection is a formidable public health challenge that can negatively impact health and well-being. We recruited a multiethnic sample of 129 gay and bisexual men living with HIV who completed a brief survey; a subset of participants completed semi-structured qualitative interviews to contextualize the data. In bivariate analyses, stigma was positively and significantly correlated with depression (r = .402, p < .001) and negatively correlated with social support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2109
2109

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Psychological problems often appear in PLWH MSM, one of which can be depression caused by high stigma (Berg & Ross, 2017; Rueda et al, 2016; Smit et al, 2012). Through family support, depression levels of PLWH MSM will decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological problems often appear in PLWH MSM, one of which can be depression caused by high stigma (Berg & Ross, 2017; Rueda et al, 2016; Smit et al, 2012). Through family support, depression levels of PLWH MSM will decline.…”
Section: Discussionmentioning
confidence: 99%
“…Religiosity is related with stigma. High stigma on PLWH MSM causes many negative impacts in daily lives, such as depression (Berg & Ross, 2017; Rueda et al, 2016; Smit, Brady, Carter, Fernandes, & Lamore, 2012). When in depression, the religiosity of PLWH MSM decrease.…”
Section: Introductionmentioning
confidence: 99%
“…The use of negative coping strategies such as safety behavior, substance use, and avoidance coping were associated with fear, stigma, and discrimination faced by PLHIV for their seropositive status and sexual identity. The overwhelming experience of being diagnosed with HIV, the negative connotation of the disease perceived by the surrounding community, and the uncertainty placed onto those who live with the diagnosis leads to substance usage, avoidance, and safety behavior (Berg et al, 2017;Cramer et al, 2015;Folkman & Lazarus, 1986). Findings from other literature reviews indicated that LGBTQ and HIV-positive people have a higher rate of abusing substances that may lead to various negative implications such as poor mental health well-being and risky behavior (Cramer et al, 2015;Hampton et al, 2010;Skeer et al, 2012) which raise an interesting observation on the role of double discrimination and stigma (Bogart et al, 2010) on this population as compared to the heterosexual group which made them more susceptible towards misusing substances.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of social support provides PLHIV a sense of belonging, worthiness, and purpose in life, which enables them to be productive members of their community and function effectively in their daily life. This resulted in positive outcomes on their mental health where they can obtain better self-confidence, autonomy, self-competence, optimism, lower level of stress and loneliness, development of social identity, and ultimately better quality of life (Berg et al, 2017;Slater et al, 2013). This review discovered that only active coping strategy reported having a positive outcome on depression and anxiety symptoms.…”
Section: Association Of Chosen Coping Strategies On Their Mental Healthmentioning
confidence: 99%
“…While a growing body of evidence has shown the links between HIV stigma and emotion dysregulation as cited above, research on HIV stigma’s direct association with substance use has been relatively scarce and has focused mostly on heterosexual samples. 2,4345 We are aware of only two studies looking at the association between HIV stigma and substance use in GBM: one which observed a non-significant association between HIV stigma and alcohol dependency, 16 and another study which found that, among young Black GBM, those with greater HIV stigma reported higher odds of having sex while high or intoxicated. 46 Further investigation in this area is therefore needed, especially given the elevated rates of drug use among HIV-positive GBM, the link between emotion dysregulation and stimulant use, 25 and the detrimental effects of use on various HIV-related health outcomes.…”
Section: Introductionmentioning
confidence: 99%